Brazilian guidelines for endovascular treatment of patients with acute ischemic stroke - Octávio Marques Pontes-Neto; Pedro Cougo; Sheila Cristina Ouriques Martins; Daniel G. Abud; Raul G. Nogueira; Maramélia Miranda; Luiz Henrique de Castro-Afonso; Leticia C. Rebello; José Guilherme M. Pereira Caldas; Rodrigo Bazan; Daniel C Bezerra; Marco Tulio Rezende; et al. (Arquivos de Neuro-Psiquiatria)
ABSTRACT These guidelines are the result of a joint effort from writing groups of the Brazilian Stroke Society, the Scientific Department of Cerebrovascular Diseases of the Brazilian Academy of Neurology, the Brazilian Stroke Network and the Brazilian Society of Diagnostic and Therapeutic Neuroradiology. Members from these groups participated in web-based discussion forums with predefined themes, followed by videoconference meetings in which controversies and position statements were discussed, leading to a consensus. This guidelines focuses on the implications of the recent clinical trials on endovascular therapy for acute ischemic stroke due to proximal arterial occlusions, and the final text aims to guide health care providers, health care managers and public health authorities in managing patients with this condition in Brazil.